2013
DOI: 10.1145/2494232.2466586
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing and modeling the impact of wireless signal strength on smartphone battery drain

Abstract: Despite the tremendous market penetration of smartphones, their utility has been and will remain severely limited by their battery life. A major source of smartphone battery drain is accessing the Internet over cellular or WiFi connection when running various apps and services. Despite much anecdotal evidence of smartphone users experiencing quicker battery drain in poor signal strength, there has been limited understanding of how often smartphone users experience poor signal strength and the quantitative impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(38 citation statements)
references
References 21 publications
0
38
0
Order By: Relevance
“…Thus, using such methods of control can improve efficiency of the networks. It is also evidenced by the studies in paper [9]. The studies conducted have shown a significant change in the signal level of mobile devices over a considerable period of use.…”
Section: Development Ofmentioning
confidence: 71%
“…Thus, using such methods of control can improve efficiency of the networks. It is also evidenced by the studies in paper [9]. The studies conducted have shown a significant change in the signal level of mobile devices over a considerable period of use.…”
Section: Development Ofmentioning
confidence: 71%
“…This can have a noticeable effect on the battery performance of a communication-heavy application [9]. The majority of devices in our dataset saw signal levels of -85 dBm or lower most of the time, with occasional spikes of good signal.…”
Section: Connectivitymentioning
confidence: 90%
“…In [8], the studied approach presented a relationship between the strength of the wireless signal and energy consumed during data transferring.…”
Section: Related Workmentioning
confidence: 99%